POLITENESS STRATEGY USED BY INDONESIAN NETIZENS ON ANIES BASWEDAN’S TWITTER AND INSTAGRAM ACCOUNT - Niadaniati Silitonga; Arsen Nahum Pasaribu (English Education Study Program Faculty of Teacher Training and Education, 2021)
This study aims to analyze the politeness strategy produced by Indonesian Netizents On Anies Baswedan’s Twitter And Instagram Account. The research design of this study is qualitative. The data of this research collected from netizens’ comments on Twitter and Instagran accounts. The data collection of this research are observing and documenting. To get the data, the researcher uses screenshot comment from Anies Baswedan’s Twitter and Instagram account. From researchers’ analysis it can be conclude that, the comments of Indonesian netizens on Anies Baswedan’s Twitter and Instagram accounts, four Politeness Strategies are used. There are Bald on Record, Positive Politeness, Negative Politeness, and Off Record. In Twitter accounts, there were 35 (33,65%) comments. In total, there are 2 (100%) Bald on Records, 13 (37,14%) Positive Politeness, 9 (25,71%) Negative Politeness, and 11 (31,42%) Off Record. While in Instagram account there were 69 (66,34%) comments. In total, not used comments in Bald on Record, 36 (52,17%) Positive Politeness, 22 (31,88%) Negative Politeness, and 11 (15,94%) Off Records. From the analysis, the researcher found that the Positive Politeness Strategy that often netizens use when commenting on Anies Baswedan’s Twitter and Instagram accounts.